Pengaruh Pemberian Alkohol terhadap Gambaran Histopatologik Aorta Tikus Wistar (Rattus norvegicus) yang Diinduksi Margarin - Kamalo, Kevin C.; Loho, Lily L.; Sambuaga, Maria K. (Universitas Sam Ratulangi, 2018)
Abstract: Margarine is a kitchen ingredient that contains trans fat which plays an important role in the formation of atherosclerosis. Alcohol is one of the compounds that can slow down the formation of foam cells which are the beginning of atherosclerotic lesions. This study was aimed to determine the effect of alcohol administration on the aortic histopathological features of Wistar rats induced by margarine. This was an experimental laboratory study. Samples were 20 Wistar rats divided into 4 groups, as follows: negative control (KN), given pellet only; positive control (KP), given pellet and margarine 5 g per day; treatment 1 (P1), given pellet, margarine 5 g, and wine (14% of alcohol) 0.18 ml per day; and treatment 2 (P2), given pellet, margarine 5 g, and wine 0.36 ml per day. All samples were terminated at day 29. Rat aortas were prepared for microscopic slides. The results showed that foam cells were found in the aortic layers. The highest number of foam cells was found in KP group, followed by P1 group, meanwhile P2 group had the lowest number of foam cells. Conclusion: In the aortas of Wistar rats given wine in moderate dose concomitantly with margarine (P1 and P2 groups), the numbers of foam cells were less than in Wistar rats that were given margarine only (KP group).Keywords: wine, histopathology of aorta, atherosclerosis, margarineÂ Abstrak: Margarin merupakan bahan dapur yang mengandung lemak trans yang sangat berperan dalam pembentukan aterosklerosis. Alkohol adalah salah satu senyawa yang dapat memperlambat pembentukkan sel busa yang merupakan awal dari lesi aterosklerosis. Penelitian ini bertujuan untuk mengetahui pengaruh dari pemberian alkohol terhadap gambaran histopatologik aorta tikus Wistar yang diinduksi margarin. Jenis penelitian ialah eksperimental laboratorik. Sampel penelitian ialah 20 ekor tikus Wistar yang dibagi atas 4 kelompok: kontol negatif (KN), hanya diberikan pelet; kontrol positif (KP) diberikan pelet dan margarin 5 gr per hari; perlakuan 1 (P1) diberikan pelet, margarin 5 gr dan minuman anggur (kandungan alkohol 14%) 0,18 ml per hari; dan perlakuan 2 (P2) diberikan pelet dan margarin 5 gr serta minuman anggur 0,36 ml per hari. Semua sampel diterminasi pada hari ke-29, dan aorta tikus diambil untuk sediaan mikroskopik. Hasil pengamatan histopatologik mendapatkan sel busa pada lapisan-lapisan aorta dengan jumlah tertinggi pada kelompok KP, kemudian P1, dan paling sedikit pada P2. Simpulan: Pada tikus Wistar yang diberikan minuman anggur dosis moderat dan margarin secara bersamaan (P1 dan P2) terlihat sel busa yang lebih sedikit dibandingkan dengan tikus Wistar yang hanya diberikan margarine (KP).Kata kunci: alkohol, histopatologik aorta, aterosklerosis, margarin